The behaviour of magnesium and its isotopes during glacial weathering in an ancient shield terrain in West Greenland - Wimpenny, J; Burton, K; James, R; Gannoun, A; Mokadem, F; Gislason, SR (2011)
The magnesium (Mg) isotope composition of rivers is sensitive to changes in the balance of primary mineral dissolution and secondary mineral formation. As these processes are regulated by climate then changes to the Earth's climate system, such as the onset of glaciation, could potentially alter the isotopic behaviour of Mg in rivers. To investigate how Mg isotopes behave during glacial weathering, we have determined the Mg concentration and Mg isotope ratio for the dissolved, suspended and bedload phases of glacial and non-glacial rivers in west Greenland. This region is essentially monolithological and there is little biological activity; hence isotope variations largely result from differences in weathering processes. Dissolved Mg in rivers is always enriched in the light Mg isotopes relative to the bedload (δ26Mg=-0.4%),and the glacial rivers have lighter Mg isotope compositions (δ26Mg -1 to -1.3%) than the non-glacial rivers (δ26Mg ~ -0.6%). Enrichment of light Mg in the dissolved load is consistent with the preferential uptake of heavy Mg from solution during the formation of secondary silicate minerals. However, evidence from saturation state modelling suggests that little secondary mineral formation is likely to have occurred in the glacial rivers because the concentration of dissolved solids is very low. Moreover, the glacial derived suspended sediment has identical Mg isotope ratios to the bedload. These observations suggest that the formation of secondary weathering minerals is not controlling the behaviour of Mg isotopes in these rivers. Rather, variations in the δ26Mg value of the dissolved load are attributed to incongruent weathering of the solid phase: preferential dissolution of carbonate minerals, which have low δ26Mg (-1.1 to -5.2%), imparts a more negative δ26Mg signal to the glacial river waters. Although our study indicates that the Mg isotopic composition of the dissolved load is sensitive to changes in weathering congruence, it is unlikely that glaciation will result in major changes in the δ26Mg composition of continental runoff. © 2011 Elsevier B.V.